GENERATIVE ARTIFICIAL INTELLIGENCE (AI) NEW VALUE PROPOSITION IN COLLEGE - Suhana Suhana; Dina Hikmayanti; Lisania Cahya Agustin; Zhanubha Cinta Aurelline (Ann Publisher, 2025)
Background. Learning technology has changed drastically. Lecturers who were previously a source of knowledge changed their role to become mentors for students. Aims. Such rapid development of AI has replaced human functions with limited memory. AI stores data indefinitely. All university lecturers and students need to know this progress, so there is a socialization event regarding the new value proposition of generative artificial intelligence on campus. Method. The method used is a presentation from the students, by students, and for students whom lecturers accompany. Result. In this presentation, it was highlighted the meaning of Gen AI, the potential of Gen AI in learning, the use of Gen AI, policies in the use of Gen AI, how the change in the educational landscape caused by the AI gene, how education is organized in the integration of AI genes, how are the applicable academic regulations in the context of the use of Gen AI, whether the use of Gen Ai will streamline the implementation of education, how to maintain the latest learning quality when utilizing AI. The use of AI in learning brings a new value proposition for learning and a new role for lecturers as education actors. Learning that utilizes AI gives students the freedom to learn anyone and anywhere across time and space. Conclusion AI supports a more personalized learning experience according to each student's needs. The presence of lecturers online and offline in the form of learning managers, student companions (cognitive presence), and student guides in interaction (social presence) provides new value to lecturers' existence in learning.